Utilization of Chitosan as an Excipient in Pharmaceutical Formulations: Systematic Literature Review - Munawaroh, Diyan Sadiatul (Devotion : Journal of Research and Community Service, 2025)
Chitosan as a biodegradable polymer extracted from crustacean waste demonstrates significant potential as an innovative excipient in pharmaceutical formulations. This systematic literature review aims to analyze recent developments in chitosan utilization as pharmaceutical excipient based on scientific evidence from 2021-2025. Research methodology employed PRISMA 2020 approach with comprehensive search through PubMed, ScienceDirect, Scopus, and Web of Science databases. From 309 identified articles, 10 articles met inclusion criteria for in-depth analysis. Results indicate that chitosan possesses multifunctional advantages as excipient with superior mucoadhesive, biodegradable, and biocompatible properties. Chitosan applications in nanoformulations, tablets, mucoadhesive systems, and inhalation powders demonstrate high flexibility across various dosage forms. Co-processed excipient technology combining chitosan with other excipients produces optimal pharmacotechnical characteristics. Integration of chitosan in 3D printing technology and nanocarriers provides innovative solutions for controlled release and targeted drug delivery. Despite showing promising prospects, chitosan implementation as excipient still requires regulatory standardization and comprehensive method validation for large-scale industrial applications in pharmaceutical green chemistry